Manufacturing technology of stone miniature columns from the Bronze Age site Gonur Depe (southern Turkmenistan) - Skakun, Natalia Nikolaevna; Terekhina, Vera Vladimirovna (Journal of Lithic Studies, 2021)
Archaeological cultures of the Bronze Age, despite the widespread use of metal, also used stone raw materials for the manufacture of tools, household, and sacred items. A lot of stone products had a complicated shape and meticulous finishing, but the technology of their manufacture is still not always clear. This fully applies to the materials of the Bronze Age of southern Turkmenistan where long-term settlements of the proto-urban type are being studied. These include Gonur Depe (2500-1500 BCE) - the administrative and religious centre of ancient Margiana (Sarianidi 2005). Among its materials are stone miniature columns of “unknown” purpose in the shape of a chess rook, which are usually found in sacral complexes. This paper deals with the technology of producing these objects (half of the collection of intact items was investigated) and is part of a collective work on a comprehensive study of large stone cult objects from Gonur Depe. The raw materials for studied miniature columns were gypsum, limestone, marbled limestone, marbled onyx, onyx, talcochlorite, and polymictic breccia. For the first time the authors made an attempt to consider the issues of miniature columns manufacturing technology. Thanks to the use-wear study of their surfaces, it became possible to reveal numerous technological traces invisible to the naked eye. The data obtained made it possible to characterize all stages of the miniature columns manufacturing technology, which indicates a high level of development of the stone-processing industry in the settlements of the Bronze Age of Turkmenistan.